Sources of Growth in Sub-Saharan Africa - Aka, Brou (IMF Working Papers; Working Paper ;, 2004)
Analysis of 1960-2002 data shows that average real GDP growth in sub-Saharan Africa was low and decelerated continuously before starting to recover in the second part of the 1990s. Growth was driven primarily by factor accumulation with little role for total factor productivity (TFP) growth. The recent pickup in economic growth was accompanied by an increase in TFP growth, namely in the group of countries whose IMF-supported programs were judged to be on track. Average annual growth in the region, at 3 1\2 percent during 1997-2002, is less than half of the estimated growth needed to halve the fraction of population living below USD 1 per day between 1990 and 2015, one of the Millennium Development Goals.